2004
DOI: 10.1073/pnas.0306466101
|View full text |Cite
|
Sign up to set email alerts
|

Gram-positive bacteria are a major reservoir of Class 1 antibiotic resistance integrons in poultry litter

Abstract: Reversing the spread of antibiotic multiresistant bacteria is hampered by ignorance of the natural history of resistance genes, the mobile elements carrying them, and the bacterial hosts harboring them. Using traditional cultivation and cultivation-independent molecular techniques, we quantified antibiotic resistance genes and mobile elements called integrons in poultry house litter from commercial poultry farms. Unexpectedly, the major reservoir for Class 1 integrons in poultry litter is not their previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
183
1
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(197 citation statements)
references
References 52 publications
8
183
1
5
Order By: Relevance
“…Especially, IncP1e plasmids such as pKJK5 have been identified as vectors of antibiotic resistance genes transfer among Proteobacteria by additionally hosting class 1 integron gene cassettes (Heuer et al, 2012). These class 1 integrons may not only spread in their originally identified Gram-negative Enterobacteriaceae hosts but can also be found among many Gram-positive bacteria (Nandi et al, 2004). Here, we demonstrated a possible direct way of accession of these class 1 integrons in Gram-positive bacteria through IncP-1e plasmid transfer from Proteobacteria.…”
Section: Medical Relevancementioning
confidence: 78%
“…Especially, IncP1e plasmids such as pKJK5 have been identified as vectors of antibiotic resistance genes transfer among Proteobacteria by additionally hosting class 1 integron gene cassettes (Heuer et al, 2012). These class 1 integrons may not only spread in their originally identified Gram-negative Enterobacteriaceae hosts but can also be found among many Gram-positive bacteria (Nandi et al, 2004). Here, we demonstrated a possible direct way of accession of these class 1 integrons in Gram-positive bacteria through IncP-1e plasmid transfer from Proteobacteria.…”
Section: Medical Relevancementioning
confidence: 78%
“…Regardless of variance within Beaver Dam Creek, intI1 was consistently more abundant across multiple microhabitats in comparison with the reference site, Meyers Branch. Culture-based and molecular estimates of intI1 abundance in bacteria of environmental origin indicate that between 1% and 10% of bacteria possess these genes (C Baker-Austin, unpublished data; Nandi et al, 2004;Boucher et al, 2007), although Biyela et al (2004) found class 1 integrons in over 50% of isolates with multiple drug resistances from an urban South African river. Variation in the proportion of a bacterial community possessing class 1 integrons outside of clinical settings is likely to be the result of several factors including (1) distance to an enriched source of class 1 integrons (for example, sewage treatment plant); (2) integron dispersal ability (for example, mobilization of the integron via physical linkage to a plasmid or transposon); (3) the taxonomic composition of the community; (4) horizontal gene transfer potential in a given habitat; and (5) intensity of selective pressure favoring the maintenance of genes contained within the integron.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have detected MGEs including plasmids, transposons and integrons across a wide variety of habitats (for example, Sobecky, 1999;Smalla and Sobecky, 2002;van Elsas and Bailey, 2002;Frost et al, 2005), but rarely in a quantitative manner due to previous methodological constraints. In those studies that did quantify MGE abundance in bacterial communities, class 1 integrase (intI1) genes were shown to be abundant in Gram-positive and Gram-negative bacteria in poultry litter obtained from farms with varying antibiotic usage regimes regardless of antibiotic usage (Nandi et al, 2004), while mercury exposure was recently demonstrated to increase the abundance of IncP-1 plasmids (Smalla et al, 2006). Yet, how MGE abundance is affected by environmental conditions and selective pressures is poorly understood and remains to be tested systematically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,30 The use of community DNA from a sample as a means for detecting antibiotic resistance genes and for identifying potential gene reservoirs is becoming more common. 1,27 However, little work has been done on the validation of this approach. The objective of the study reported here was to determine the specific level at which antibiotic resistance genes can be detected within community DNA prepared from cattle fecal samples.…”
Section: Introductionmentioning
confidence: 99%